Analisis Strategi Inovasi Produk dalam Meningkatkan Penjualan (Studi Kasus Kipang Pulut Bonjol Ita Kabupaten Pasaman) - Sinta Junia; Rika Widianita (ARZUSIN, 2026)
Product innovation strategy is an important factor in increasing the competitiveness and sales of micro, small, and medium enterprises (MSMEs). Although product innovation in MSMEs has been widely examined, studies that specifically analyze product innovation strategies in traditional food industries based on local wisdom, particularly Kipang Pulut Bonjol in Pasaman Regency, remain limited. This study aims to analyze the product innovation strategy implemented by the Kipang Pulut Bonjol Ita enterprise in increasing sales. This study used a qualitative approach with a case study design. The informants consisted of the business owner, employees, and consumers selected using purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and were then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing and verification. The results show that product innovation strategies are carried out through improving product quality, developing product variations, and updating packaging style and design. These strategies are able to increase product added value, strengthen business competitiveness, and enhance product appeal in the eyes of consumers. However, consumer preferences for the original variant, limited production capacity, and marketing reach indicate that sales improvement has not yet occurred optimally. These findings contribute to the development of studies on product innovation in traditional food MSMEs and expand understanding of the application of innovation strategies in increasing the competitiveness of businesses based on local potential. The conclusion of this study emphasizes the importance of sustainable product innovation as an MSME development strategy. The implications of this study can serve as input for business actors and stakeholders in designing programs to strengthen traditional food product innovation based on local wisdom.